2008
DOI: 10.1016/j.cub.2008.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Physical Mechanisms Redirecting Cell Polarity and Cell Shape in Fission Yeast

Abstract: Summary The fission yeast Schizosaccharomyces pombe has a cylindrical rod-shape that is organized and maintained by interactions between the microtubule, cell membrane, and actin cytoskeleton; i.e., microtubules deliver factors to the cell tips that subsequently recruit the actin machinery to direct localized cell growth [1]. Mutations affecting any components in this pathway lead to bent, branched, or round cells [2]. In this context, the cytoskeleton controls cell polarity and thus dictates cell shape. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 30 publications
4
75
0
1
Order By: Relevance
“…Dynamic landmarks activate autocatalytic actin polymerization: presumably, actin filaments in cables and patches further recruit actin nucleators. This could be consistent with experiments suggesting positive feedback in the polarization system (Terenna et al, 2008). Autocatalytic polymerization amplifies local noise, polarizing the cell and breaking symmetry.…”
Section: Models Of Polarized Cell Growth and Netosupporting
confidence: 90%
See 2 more Smart Citations
“…Dynamic landmarks activate autocatalytic actin polymerization: presumably, actin filaments in cables and patches further recruit actin nucleators. This could be consistent with experiments suggesting positive feedback in the polarization system (Terenna et al, 2008). Autocatalytic polymerization amplifies local noise, polarizing the cell and breaking symmetry.…”
Section: Models Of Polarized Cell Growth and Netosupporting
confidence: 90%
“…Since shorter microtubules are more stable, more force comes from the closer tip and the microtubule system centers the nucleus, as suggested by an earlier computational model (Tran et al, 2001). These results extend easily to microtubule dynamics in differently shaped cells, such as those in recent experiments where they are confined (Minc et al, 2009;Terenna et al, 2008). …”
Section: Models Of Interphase Cytoskeletal Subcomponents: Microtubulessupporting
confidence: 69%
See 1 more Smart Citation
“…In 2008 already Terenna et al (2008) grew fission yeast in microfabricated channels and showed directly how cell shape and microtubule organization are coupled and control cell polarity. The most dramatic changes in cell shape were created by Minc et al (2011).…”
mentioning
confidence: 99%
“…1b). 29,30 Unlike in the GTPase-based system, the energy necessary to maintain diffusion-counteracting self-focusing mechanism is consumed not within the cluster itself, but rather by the polymerizing microtubules (GTP) and molecular motors (ATP) that move along the several nuclear pore complex and vesicle coat proteins including COPI, COPII and clathrin. 21,22 While these proteins are remarkably diverse in the way they interact with each other, all of them are capable of forming spatially extended polymeric lattices.…”
mentioning
confidence: 99%